2016
DOI: 10.2118/174784-pa
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning as a Reliable Technology for Evaluating Time/Rate Performance of Unconventional Wells

Abstract: Summary Production-data analysis is a practice fraught with inconsistencies. In the application of any single model, the quantity of answers arrived at by experienced evaluators is often equal to the number of evaluators analyzing the data. The cause of such inconsistency is bias on the part of evaluators. Although the colloquial use of bias typically implies systematic error, in this paper, we define bias as an expression of belief by the evaluator. With the lack of recognition of bias, no mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Bayes's Theorem [58] has been widely used for uncertainty quantification [59][60][61][62]. Gong et al [59] introduced a Bayesian probabilistic methodology using Markov chain Monte Carlo (MCMC) coupled with the standard Metropolis-Hasting (MH) algorithm [63,64].…”
Section: Probabilistic Decline Curve Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Bayes's Theorem [58] has been widely used for uncertainty quantification [59][60][61][62]. Gong et al [59] introduced a Bayesian probabilistic methodology using Markov chain Monte Carlo (MCMC) coupled with the standard Metropolis-Hasting (MH) algorithm [63,64].…”
Section: Probabilistic Decline Curve Modelmentioning
confidence: 99%
“…Applying the new method to 197 Barnett shale gas wells, the authors concluded that their methodology can quantify the uncertainty in hindcasted production with a narrower P90-P10 interval and higher computational efficiency than the modified bootstrap method [65], which was originally proposed by Jochen and Spivey [66]. A Bayesian machine learning method with the MCMC coupled with the MH algorithm was proposed in Fulford et al [60], and was used to forecast production in shale wells by utilizing the transient hyperbolic model introduced by Fulford and Blasingame [67]. However, the behavior of b and D parameters as a function of time is only valid for homogeneous reservoirs with equal fracture half-length and spacing, not suitable for heterogeneous reservoirs with varying fracture half-length and spacing [68].…”
Section: Probabilistic Decline Curve Modelmentioning
confidence: 99%
“…The Arps (1945) decline-curve family has been widely applied in the industry to estimate reserves. This practice also has been extended to unconventional reservoirs (Gong et al 2014), where the hyperbolic model is the most suitable to capture the production decline during the transient state:…”
Section: Horizontal Wellmentioning
confidence: 99%
“…When investing in a field-development plan, it is essential to be aware of the risks taken and determine a probable range of reserves volumes. For this reason, uncertainty-quantification algorithms have been widely applied to decline-curve analysis (Cronquist 1991;Chang and Lin 1999;Cheng et al 2008;Gong et al 2014;Fulford et al 2016;Yu et al 2016). Purvis and Kuzma (2016) provides an overview of methods commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…To make things worse, the empirical DCA fits of particular wells are ill-suited to forecasting production from a wide area of a given shale play in which reservoir properties vary and uncertainties abound. Therefore, some authors have developed probabilistic models to introduce a range of possible outcomes into their production forecasts [15][16][17][18][19]. The most common assumption is that well productivities in shales are log-normally distributed.…”
Section: Introductionmentioning
confidence: 99%